2019
DOI: 10.3390/w11112208
|View full text |Cite
|
Sign up to set email alerts
|

Solute Transport and Transformation in an Intermittent, Headwater Mountain Stream with Diurnal Discharge Fluctuations

Abstract: P.J.B.); J.Drummond@bham.ac.uk (J.D.D.); D.M.HANNAH@bham.ac.uk (D.M.H.); S.Krause@bham.ac.uk (S.K.); a.m.milner@bham.ac.uk (A.M.)Abstract: Time-variable discharge is known to control both transport and transformation of solutes in the river corridor. Still, few studies consider the interactions of transport and transformation together. Here, we consider how diurnal discharge fluctuations in an intermittent, headwater stream control reach-scale solute transport and transformation as measured with conservative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 118 publications
(155 reference statements)
1
19
0
Order By: Relevance
“…This Special Issue consists of 20 original research papers . The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue consists of 20 original research papers . The majority of the contributions [3,5,[8][9][10][11][15][16][17][19][20][21][22][23] focus on the interactions between rivers or streams and groundwater. Three studies [6,13,14] investigate the interactions between lakes and groundwater, while two studies [4,18] deal with the exchange between groundwater and oceanic water.…”
Section: Overview Of the Special Issue Contributionsmentioning
confidence: 99%
“…While most studies presented in this Special Issue focus on the investigation of exchange fluxes across groundwater-surface water interfaces, there are a few that focus additionally on biogeochemical processes at the interface. Ward et al [20] used the resazurin-resorufin reactive tracer system to study aerobic microbial transformation at sediment-water interfaces and found that the resazurin-to-resorufin transformation rate was highest in youngest storage locations (i.e., that increasing residence times do not necessarily increase the reaction potential of solutes). Wolke et al [21] systematically studied the impact of bed form movements on oxygen dynamics in the hyporheic zone.…”
Section: Hyporheic Zone Studiesmentioning
confidence: 99%
“…Thus, the rate of Raz-Rru transformation represents an integrated measure of (near-instantaneous) whole-system aerobic ER. The Raz-Rru system has been used broadly to assess the reactivity of stream reaches and to identify the portion of transient storage that is metabolically active (Argerich et al 2011, González-Pinzón et al 2012, Blaen et al 2018, Ward et al 2019. Second, we calculated nitrate and TDP retention downstream of the WWTP inputs at sub-daily timescales based on longitudinal declines in concentration (Martí et al 2004).…”
Section: Experimental Designmentioning
confidence: 99%
“…To determine transfer functions for the sub-reaches between fluorometers, we used the nonparametric deconvolution approach described in Cirpka et al (2007), and the associated MATLAB ® code (The MathWorks ® , Natick, Massachusetts), to analyze injection input signal and conservative tracer BTCs. To characterize and compare this transport and storage behavior between study reaches, we calculated a series of transport and transient storage metrics for each sub-reach transfer function, following the equations in Ward et al (2016Ward et al ( , 2019 and Schmadel et al (2016). Metrics included the 1 st temporal moment (M 1 , h), representing the mean travel time; the 2 nd central temporal moment (m 2 , h 2 ), representing the temporal variance or symmetrical spread-ing; the 3 rd central temporal moment (m 3 , h 3 ), representing the temporal extent of late-time tailing; the coefficient of variation (CV), representing symmetrical spreading relative to travel time; skewness (ɣ), representing asymmetrical latetime tailing; and apparent dispersion (D app , m 2 /h).…”
Section: Stream Solute Tracer Injectionsmentioning
confidence: 99%
“…For example, mapping the spatial distribution of hydrologic behaviors aids in quantifying the temporal stability of soil water storage (Lee and Kim, 2019) and water transit time distributions (Harman, 2015). These are both key factors that complicate hillslope modeling studies (Kirchner, 2016;Guio Blanco et al, 2018) and efforts to quantify chemical export from the CZ (Ward et al, 2019). Furthermore, different hydrologic behaviors may map to important ecosystem control points (Bernhardt et al, 2017)-areas that support continuously or periodically high rates of biogeochemical cycling (Darrouzet-Nardi and Bowman, 2011;Knowles et al, 2015;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%